Statistical Analysis for Revealing Defects in Software Projects: Systematic Literature Review - Mahmoud, Alia Nabil (2021)
Mahmoud, A. N., & Santos, V. (2021). Statistical Analysis for Revealing Defects in Software Projects: Systematic Literature Review. International Journal of Advanced Computer Science and Applications, 12(11), 237-249. https://doi.org/10.14569/IJACSA.2021.0121128